Alterations of the Gut Microbiome in Chinese Zhuang Ethnic Patients with Sepsis - Yu, Jieyang; Li, Hongping; Zhao, Jingjie; Huang, Yanhua; Liu, Chunlei; Yang, Pengfei; Lu, Dinggui; Song, Jian; Meng, Lingzhang (Mediators of Inflammation, 2022)
Objectives. Sepsis is characterized as a dysregulated host immune response to infection and has been known to be closely associated with the gut microbiome. This study was aimed at investigating the gut microbial profiles of Zhuang ethnic patients with sepsis. Method. Eleven Zhuang ethnic patients with sepsis and 20 healthy individuals (controls) were recruited at the Baise City People’s Hospital, China. Their gut microbial community profiles were analyzed by 16S rRNA gene sequencing using the Illumina MiSeq system. Results. The gut microbial community of patients with sepsis was significantly altered compared to that of the healthy individuals based on the results of principal coordinate analysis and microbial ecological networks. Additionally, significantly lower microbial alpha diversity was observed in patients with sepsis than in healthy individuals. In particular, the enrichment of Bilophila, Burkholderia, Corynebacterium, and Porphyromonas, along with the reduced abundance of a large number of short-chain fatty acid-producing microbes, including Roseburia, Bifidobacterium, Faecalibacterium, Coprococcus, Blautia, Clostridium, Ruminococcus, and Anaerostipe was observed in patients with sepsis compared to the control group. Moreover, patients with sepsis could be effectively classified based on the abundance of these bacteria using a support vector machine algorithm. Conclusion. This study demonstrated significant differences in the gut microbiome between Zhuang ethnic patients with sepsis and healthy individuals. In the future, it is necessary to determine whether such alterations are the cause or consequence of sepsis.